Kajian Hukum Hindu Dan Hukum Humaniter Internasional Tentang Perlindungan Pihak Medis Dalam Konflik Bersenjata - Widnyana, I Made Adi (Jayapangus Press, 2023)
The protection of medical personnel in armed conflict is often neglected. All countries in the world must pay attention to this by establishing international humanitarian law. Protection policies for medical personnel in war should reflect the values of past religious teachings, one of which is in the Hindu books Arthasastra and Bharatayuda, some of which reflect humanitarian missions. The purpose of this research is to demonstrate the concept of protection for medical personnel in situations of armed conflict in international humanitarian law policy and to analyze the virtues in the Book of Arthasasta and the Bharatayuda war epic. The method uses normative research with a legal and historical regulatory approach which is analyzed descriptively. The research results show that the role of medical personnel in armed conflict situations is very important, guided by international charters. In the Hindu Law Book Arthasasta states that the protection of medical personnel in conflict situations is the responsibility of the king or policy maker to provide a safe place, so that they can carry out their duties well. In the Bharatayuda epic, it is also told that Nakula and Sahadeva were protected by enemy troops to provide treatment to the injured Karna. The values contained in the teachings of Hinduism are one of the philosophies of protection for medical personnel in the current situation of armed conflict. These values are then championed in international humanitarian law policies regarding the importance of protecting the weak and those who carry out humanitarian missions.